Trabajo infantil y logro de aprendizaje en estudiantes del cuarto y quinto ciclo de nivel primaria en la IEP N° 6010148 Balbina Soto Correa, Caballococha 2022 - Arbildo Morales, Aquiles (2025)
The study focused on examining the relationship between child labor and academic achievement among fourth and fifth cycle primary students at IEP N° 6010148 Balbina Soto Correa in Caballo Cocha during 2022. A relational, cross-sectional, and bivariate field design was implemented, utilizing a sample of 96 students. Data collection was carried out through observation and documentary analysis, using a questionnaire guide and a grade record, both validated by expert judges prior to implementation. Upon analyzing the results, a p-value of .000 was obtained, which was below the significance level of .05. This allowed for the rejection of the null hypothesis and confirmed the existence of a significant relationship between child labor and academic achievement. The correlation coefficient (rho = -.566) indicated a moderate negative relationship, suggesting that a negative perception of child labor is associated with higher academic achievement among the students.